1996
DOI: 10.1002/j.1460-2075.1996.tb00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Daunorubicin-induced apoptosis: triggering of ceramide generation through sphingomyelin hydrolysis.

Abstract: The nature of the signaling pathway(s) which initiate drug‐triggered apoptosis remains largely unknown and is of fundamental importance in understanding cell death induced by chemotherapeutic agents. Here we show that in the leukemic cell lines U937 and HL‐60, daunorubicin, at concentrations which trigger apoptosis, stimulated two distinct cycles of sphingomyelin hydrolysis (approximately 20% decrease at 1 microM) within 4–10 min and 60–75 min with concomitant ceramide generation. We demonstrate that the incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
240
2
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(253 citation statements)
references
References 45 publications
10
240
2
1
Order By: Relevance
“…A number of extracellular stimuli, not only various cytokines including tumor necrosis factor (TNF)-a, interferon-g (Kim et al, 1991;Dressler et al, 1992), interleukin-1b (Ballou et al, 1992), nerve growth factor (Dobrowsky et al, 1994), and activators of Fas receptor (Cifone et al, 1994), but also physical stresses including heat shock, irradiation and chemotherapeutic drugs (Verheij et al, 1996;Santana et al, 1996;Ja rezou et al, 1996) are shown to cause sphingomyelin (SM) hydrolysis via sphingomyelinase (SMase), leading to elevation of intracellular ceramide, although several recent reports have questioned the role of ceramide in apoptosis induced by Fas or TNF-a (Sillence and Allen, 1997; Hsu et al, 1998;Watts et al, 1997Watts et al, , 1999a. The addition of exogenous ceramide has been associated with several antiproliferative responses including cell di erentiation, apoptosis, and cell cycle arrest (Okazaki et al, 1990;Kolesnick and Hannun, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A number of extracellular stimuli, not only various cytokines including tumor necrosis factor (TNF)-a, interferon-g (Kim et al, 1991;Dressler et al, 1992), interleukin-1b (Ballou et al, 1992), nerve growth factor (Dobrowsky et al, 1994), and activators of Fas receptor (Cifone et al, 1994), but also physical stresses including heat shock, irradiation and chemotherapeutic drugs (Verheij et al, 1996;Santana et al, 1996;Ja rezou et al, 1996) are shown to cause sphingomyelin (SM) hydrolysis via sphingomyelinase (SMase), leading to elevation of intracellular ceramide, although several recent reports have questioned the role of ceramide in apoptosis induced by Fas or TNF-a (Sillence and Allen, 1997; Hsu et al, 1998;Watts et al, 1997Watts et al, , 1999a. The addition of exogenous ceramide has been associated with several antiproliferative responses including cell di erentiation, apoptosis, and cell cycle arrest (Okazaki et al, 1990;Kolesnick and Hannun, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Daunorubicin (DNR) has been shown to elicit ceramide generation (Bose et al, 1995;Jaffrezou et al, 1996), and as ceramide catabolism limits its participation in apoptotic pathways, we determined whether DNR regulates the activities of enzymes that metabolize ceramide. DNR dose dependently caused a rapid and selective activation of acid CDase in HepG2 cells, reaching a maximum at 30 min after drug treatment, without effect on the neutral/alkaline CDases (Figure 1a,b).…”
Section: Dnr Activates Acid Cdase In Hepatoma Cellsmentioning
confidence: 99%
“…This is evidenced by numerous cell-based and animal studies showing the ability of ceramide to induce cell cycle arrest or apoptosis (9)(10)(11). Furthermore, ceramide has been shown to function as a key mediator of apoptosis brought on by stress-inducing therapeutic agents, such as anthracyclines (11)(12)(13)(14), ionizing radiation (15,16), tumor necrosis factor (TNF)-related apoptosis-inducing ligand (17), and paclitaxel (18). Reciprocally, the inhibition of ceramide production by compounds such as the ceramide synthase inhibitor fumonisin B1 or by small interfering RNA approaches has been shown to abrogate stress-induced apoptosis (11,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…The modulation of ceramide levels (a) by stress-inducing agents (11)(12)(13)(14)(15)(16)(17)(18) or (b) as noted in multiple primary tumor types (reviewed in refs. 3,22) is likely to result due to multiple changes in the regulation of ceramide-metabolizing enzymes or pathways; however, the exact molecular mechanisms responsible for these alterations remain unclear.…”
Section: Introductionmentioning
confidence: 99%